Peran Penting Insan Genre Gajah Mada Kota Mojokerto Mempersiapkan Generasi Berencana Menuju Indonesia Emas Tahun 2045 - Muhamad Abiedama Fahrezi; Ni Putu Gita Jayanti Savitri (Lembaga Pengembangan Kinerja Dosen, 2024)
Towards Indonesia Gold 2045, teenagers need to be equipped to contribute beneficially to the country. They are important assets as they will inherit and continue the nation's struggle in the future. Many things need to be achieved, both internally among the teenagers and externally in aspects related to forming high-quality teenagers. GenRe (Planned Generation) is a program aimed at supporting teenagers transitioning to adulthood through educational, career, and family planning. This research uses a quantitative approach with a survey method to evaluate the effectiveness of the Insan Genre Gajah Mada program in preparing a planned generation towards Indonesia Gold 2045. From this program, various innovations provide opportunities to build relationships, gain experiences, and enhance the creativity of teenagers, preparing them to face Indonesia Gold 2045.